Nominal growth of a small open economy - Péter Benczúr; István Kónya (Hungarian Academy of Sciences, Institute of Economics, 2006)
This paper develops a flexible price, two-sector nominal growth model, in order to study the nominal aspects of capital accumulation (convergence). We adopt a classical model of a small open economy with traded and nontraded goods, and enrich its structure with gradual investment and a preference for real money holdings. This latter is motivated by the fact that a large fraction of less developed OECD country (in particular: new EU members) households' assets are local currency bank deposits. The modelling framework gives the following results: (1) the flexibility of the monetary regime (whether money or the exchange rate is allowed to fluctuate freely) matters; (2) under imperfect floating (like in a currency board), the level of the exchange rate has a medium-run impact on nominal and real variables but no long-run real effect; (3) along the real equilibrium path (which can be implemented by flexible exchange rates), capital accumulation implies an increase in the price of nontradables (a real appreciation); (4) under flexible exchange rates, capital accumulation also implies a nominal appreciation.
Keywords: F32; F41; F43; 330; two-sector growth model; household portfolios; q-theory; real effects of nominal shocks; equilibrium real exchange rates; Kleine offene Volkswirtschaft; Wachstumstheorie; Wirtschaftswachstum; Wechselkurs; Investition; Theorie